Complications of Diabetes Mellitus with Diabetic Foot Syndrome - Alijonov D.A.; Bektasheva G.M.; Kholmatova G.A. (Scholars Digest Publishing, 2023)
Diabetes mellitus (DM) is one of the most common chronic diseases in the world. Recently, this disease has begun to be studied as a social problem that is becoming more and more urgent. This is due to the fact that there is an increase in the number of people suffering from diabetes mellitus, the chronic nature of the course of the disease, the development of various complications that lead to a decrease in the quality of life and a reduction in its duration.
Keywords: Diabetic foot syndrome (SDS), disability, arterial hypertension, dyslipidemia, nephropathy and retinopathy.